Strategy and globalization - Moore, Karl 1955-; Hébert, Louis (Contemporary issues in business and globalization, 2008)
This major reference work contains key research articles that offer insight into the fields of strategy and globalization. Strategy and Globalization addresses strategic thinking as it as evolved over recent years and the strategic challenges and opportunities presented by globalization.